Atopic Dermatitis Studies through In Vitro Models - De Vuyst, Evelyne; Salmon, Michel; Evrard, Céline; Lambert de Rouvroit, Catherine; Poumay, Yves (Frontiers in Medicine, 2017)
Atopic dermatitis (AD) is a complex inflammatory skin condition that is not fully understood. Epidermal barrier defects and Th2 immune response dysregulations are thought to play crucial roles in the pathogenesis of the disease. A vicious circle takes place between these alterations, and it can further be complicated by additional genetic and environmental factors. Studies investigating in more depth the etiology of the disease are thus needed in order to develop functional treatments. In recent years, there have been significant advances regarding in vitro models reproducing important features of AD. However, since a lot of models have been developed, finding the appropriate experimental setting can be difficult. Therefore, herein, we review the different types of in vitro models mimicking features of AD. The simplest models are two-dimensional culture systems composed of immune cells or keratinocytes, whereas three-dimensional skin or epidermal equivalents reconstitute more complex stratified tissues exhibiting barrier properties. In those models, hallmarks of AD are obtained, either by challenging tissues with interleukin cocktails overexpressed in AD epidermis or by silencing expression of pivotal genes encoding epidermal barrier proteins. Tissue equivalents cocultured with lymphocytes or containing AD patient cells are also described. Furthermore, each model is placed in its study context with a brief summary of the main results obtained. In conclusion, the described in vitro models are useful tools to better understand AD pathogenesis, but also to screen new compounds in the field of AD, which probably will open the way to new preventive or therapeutic strategies.